Afterword: Expertise in Our Time - Cummings, Maggie (Anthropologica, 2013)
What do we talk about when we talk about exper tise? What does it mean to be an expert? Who decides what counts as expertise and what does not? Today, at a time when we are awash in digital informa tion, often to the point of information overload, these questions reflect a kind of expertise anxiety that may well be a hallmark of the contemporary, so-called digital age. This anxiety is exacerbated (especially, I would argue, among academics), by what I think of as exper tise inflation: we live in a time when it seems like almost anyone with Internet access, a well-curated blog, clever branding and enough interest, can be a self-proclaimed expert on almost any topic. It is no accident that, after reading the collected articles in this issue, I was inspired to think about contested perspectives on expertise as a sign of our times—both the epochal time of the digital age and the turbulent times, as Annelise Riles (2013) called them in her keynote address to the Canadian Anthropological Society—post-2008 market meltdown. The key contribution the authors in this thematic section make to the anthropology of knowledge is not only their close attention to the production and circulation of various modes of expertise; rather, what makes these articles so compelling and, indeed, so timely is their insistence that expert knowledge is always bound up with temporality. Expert knowledge, as Alexandra Widmer points out in her introduction, becomes expert knowledge precisely by "mobilizing and naturalizing ex periences of time" and by compelling people "to orient themselves in time in particular ways."